Quantifying positional and temporal movement patterns in professional rugby union using global positioning system - Jones, M. R.; West, D. J.; Crewther, B. T.; Cook, C. J.; Kilduff, L. P. (European Journal of Sport Science, 2015)
This study assessed the positional and temporal movement patterns of professional rugby union players during competition using global positioning system (GPS) units. GPS data were collected from 33 professional rugby players from 13 matches throughout the 2012-2013 season sampling at 10 Hz. Players wore GPS units from which information on distances, velocities, accelerations, exertion index, player load, contacts, sprinting and repeated high-intensity efforts (RHIE) were derived. Data files from players who played over 60 min (n = 112) were separated into five positional groups (tight and loose forwards; half, inside and outside backs) for match analysis. A further comparison of temporal changes in movement patterns was also performed using data files from those who played full games (n = 71). Significant positional differences were found for movement characteristics during performance (P < 0.05). Results demonstrate that inside and outside backs have greatest high-speed running demands; however, RHIE and contact demands are greatest in loose forwards during match play. Temporal analysis of all players displayed significant differences in player load, cruising and striding between halves, with measures of low- and high-intensity movement and acceleration/deceleration significantly declining throughout each half. Our data demonstrate significant positional differences for a number of key movement variables which provide a greater understanding of positional requirements of performance. This in turn may be used to develop progressive position-specific drills that elicit specific adaptations and provide objective measures of preparedness. Knowledge of performance changes may be used when developing drills and should be considered when monitoring and evaluating performance.